KEMAMPUAN RAMAL SISTEM PERKIRAAN IKLIM MUSIMAN MENGGUNAKAN FENOMENA ENSO DI KABUPATEN LOMBOK TENGAH, NUSA TENGGARA BARAT - Ismail Yasin; Lara MigaWahyuni; Mahrup (Jurnal Cakrawala Ilmiah, 2023)
Lombok Island, particularly the southern central part of Lombok, often experiences droughts that result in failed cultivation or harvests due to the El Nino and Southern Oscillation (ENSO) phenomena. Therefore, the objective of this research is to determine the forecasting skill or predictive ability of a seasonal climate prediction system using the ENSO indicator in the Central Lombok regency, West Nusa Tenggara Province. This study employs a descriptive method by comparing the average rainfall in El Nino years with non-El Nino years. The research is conducted in the Central Lombok regency, which is divided into the northern and southern parts. The data used includes monthly precipitation recorded by BMKG for approximately 50 years (1970-2019) in all districts of Central Lombok. The SOI data is accessed at http://www.bom.gov.au/climate/current/soi2.shtml. The results of this study indicate that the use of the ENSO indicator to forecast seasonal rainfall patterns in the Central Lombok regency shows high consistency and significant predictive ability. There is no significant difference in the predictive ability and consistency of the forecast results between the northern and southern parts of Central Lombok. In general, the predictive ability during the dry season exhibits higher consistency (25%) compared to the rainy season (14%).